Pendekatan Berbasis Pola Asuh Orang Tua dalam Mengatasi Social Withdrawal Pada Anak - Titi Sahidah Fitriana (Jurnal Psikologi Tabularasa, 2015)
Social withdrawal is a consistent tendency to be alone with anxiety when dealing with others. Social withdrawal in children who are not handled properly can cause communication barriers, emotional regulation and lack of problem solving abilities. In the long run, socially withdrawn children have a greater risk of having low self-adjusting abilities, difficulty interacting with peers and difficulties in school. The development of social withdrawal in children, was influenced by genetic factors and environmental factors. Parents has a very important role in tackling the growth of social withdrawal in children. The approaches include developing secure attachment with children, encouraging them to socialize, helping them to regulate and express their emotions and provide opportunities to engage in activities which they excel and make them more valuable and willing to engage in interpersonal relationships.